2021
DOI: 10.1111/jvp.12993
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of transdermal flunixin meglumine and effects on biomarkers of inflammation in horses

Abstract: Flunixin meglumine is a highly efficacious nonsteroidal anti‐inflammatory drug commonly used in equine medicine and especially in performance horses. Recently, a new transdermal flunixin meglumine product has been approved for use in cattle. Although not currently approved for use in the horse, the convenience of this product may prove appealing for use in horses, warranting study. Six horses were administered a single transdermal dose of 500 mg and blood and urine samples collected for up to 96 h post‐adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“… 19 , 20 Recently, a study has evaluated the pharmacokinetics of a bovine transdermal formulation of flunixin meglumine in horses. 21 In this study, transdermal administration (500 mg) was well tolerated in horses with no adverse effects noted. The maximum systemic concentration of flunixin meglumine was lower and the time to maximum absorption was longer than reported for oral and intramuscular administration; however, inhibition of COX‐1 and COX‐2 was identified for 24‐72 hours post administration.…”
Section: Introduction: Role Of Nsaid S In Manageme...mentioning
confidence: 64%
See 3 more Smart Citations
“… 19 , 20 Recently, a study has evaluated the pharmacokinetics of a bovine transdermal formulation of flunixin meglumine in horses. 21 In this study, transdermal administration (500 mg) was well tolerated in horses with no adverse effects noted. The maximum systemic concentration of flunixin meglumine was lower and the time to maximum absorption was longer than reported for oral and intramuscular administration; however, inhibition of COX‐1 and COX‐2 was identified for 24‐72 hours post administration.…”
Section: Introduction: Role Of Nsaid S In Manageme...mentioning
confidence: 64%
“…Injectable flunixin meglumine is labelled for intravenous or intramuscular injection; however, intramuscular administration should be avoided due to the risk of development of clostridial myonecrosis 19‐20 . Recently, a study has evaluated the pharmacokinetics of a bovine transdermal formulation of flunixin meglumine in horses 21 . In this study, transdermal administration (500 mg) was well tolerated in horses with no adverse effects noted.…”
Section: Introduction: Role Of Nsaids In Management Of Orthopaedic Painmentioning
confidence: 95%
See 2 more Smart Citations
“…Only a few studies have reported successful transdermal delivery of NSAIDs in animals, including ketoprofen in cattle [ 26 ] and pigs [ 27 ], and flunixin meglumine in horses [ 28 ], goats [ 29 ], and piglets [ 30 ]. Some studies targeted local penetration only, including naproxen [ 31 ], methyl salicylate [ 32 ], meloxicam [ 33 ], and celecoxib [ 34 ].…”
Section: Introductionmentioning
confidence: 99%